STATUS TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI - Ruslang; Ery Wardanengsih; Lisna; Nirmawati Darwis; Abdul Ba’iz Mus’ing (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2023)
One of the main issues facing global health today is hypertension. Among the top five nations in the world for the proportion of senior population is Indonesia. According to estimates, there will be 36 million elderly people in Indonesia by 2025, and hypertension will be a major health issue. According to preliminary research survey data, there are twenty-one elderly in Nepo Village who suffer from hypertension. The purpose of this study was to ascertain the blood pressure status of Nepo Village's elderly hypertensive residents. At the time of the investigation, the sample size for this descriptive method utilising a quantitative approach and total sampling methodology which was based on inclusion and exclusion criteria was 21 respondents. Tensimeters and observation sheets are used in the data collection process. According to the study's findings, the majority of respondents had systolic blood pressure measured between 140 and 159 mmHg in 11 (52.4%) of the cases and diastolic blood pressure measured between 90 and 99 mmHg in 10 (47.5%) of the cases. The study's findings indicate that there is a correlation between gender and age in the blood pressure condition of elderly hypertensive patients.